Parabacteroides distasonis alleviates enterotoxigenic Escherichia coli-induced diarrhea in mice by mediating gut microbiota - Chen, Hongliang; Gong, Jinshuo; Wang, Jia; Li, Yang; Yang, Wenjie; Guo, Jianan; Wang, Jie; Wang, Yongxiang; Zhou, Lu; Zhang, Lei; Shi, Chunwei; Zhang, Di (Frontiers in Microbiology, 2026)
Enterotoxigenic Escherichia coli (ETEC) is among the major pathogens responsible for diarrhea in young piglets, leading to significant economic losses. Elucidating the interaction between gut microbiota and ETEC is crucial for developing alternative therapeutics that do not rely on antibiotics. This study aimed to investigate the mitigative effects of Parabacteroides distasonis on ETEC-induced diarrhea in a mouse model. Twenty-four SPF female BABL/c mice were equally allocated into four treatment groups: sham challenge (CON), Escherichia coli K88 challenge (ETEC), P. distasonis treatment with ETEC K88 challenge (PD), and E. coli Nissle 1917 treatment with ETEC K88 challenge (ECN) groups. The experiment lasted for 14 days, spinning from 8 days before to 6 days after the first ETEC K88 challenge (day 9). The mice in the ETEC, PD and ECN groups were gavaged with ETEC for 5 consecutive days with a dosage of 2 × 109 CFU twice per day, whereas the PD and ECN groups were inoculated with 2 × 108 CFU P. distasonis and E. coli Nissle 1917 once per day, respectively. Both reverse transcription PCR and western blotting revealed significantly increased levels of tight junction proteins (ZO-1, occludin and claudin-1) and ELISA exhibited significantly decreased TNF-α, IL-1β and IL-8 levels. Histopathological analysis revealed that P. distasonis repaired intestinal damage and restored villus length caused by ETEC infection. Furthermore, 16S RNA sequencing indicated that gut microbiota dysbiosis was ameliorated by enhancing the abundance of beneficial bacteria the Lachnospiraceae_NK4A136_group and B. uniformis. Overall, our study suggested that P. distasonis could alleviate ETEC-induced diarrhea by restoring intestinal barrier integrity, and regulating gut microbiota and proinflammatory cytokines, which serves as an alternative strategy to control ETEC infection.